The depreciation-policy decisions of industrial firms: tax benefits versus non-tax costs - Τζόβας Χρήστος (SPOUDAI Journal of Economics and Business, 2005)
Empirical research has indicated that when firm's management makes accounting-policy decisions, it may have to trade-off the tax benefits relating with a particular decision against the non-tax costs ensuing from it. The applicability of this argument is examined within the context of the Greek business sector, with special reference to the depreciation-policy decisions of industrial firms operating in Greece. In particular, this paper investigates whether the firms' ownership/control status, and their leverage characteristics, influences the balance of the non-tax costs and the tax benefits. Furthermore, the influence of the size of the firm on its accounting-policy decisions is investigated. In addition, it has been examined whether the firms' depreciation-policy decisions constitute a part of a tax-reducing strategy aiming at reducing firm's long time taxable income by substituting alternative tax shields over time. For the investigation of these issues, the financial statements of a sample of industrial firms operating in Greece have been analysed. The findings of this analysis suggest that firms' leverage characteristics and their size can explain certain aspects of firms' depreciation-policy decisions. JEL Classificatision: M41